2006
DOI: 10.1103/physrevb.74.195338
|View full text |Cite
|
Sign up to set email alerts
|

Linear polarization of the photoluminescence of quantum wells subject to in-plane magnetic fields

Abstract: The degree and orientation of the magnetic-field induced linear polarization of the photoluminescence from a wide range of heterostructures containing (Cd,Mn)Te quantum wells between (Cd,Mn,Mg)Te barriers has been studied as a function of detection photon energy, applied magnetic field strength and orientation in the quantum well plane. A theoretical description of this effect in terms of an in-plane deformation acting on the valence band states is presented and is verified by comparison with the experimental … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The first term in the above Hamiltonian will be further called Zeeman part of the LK Hamiltonian because of its similarity to standard Zeeman Hamiltonian. It is well known from studies of quantum wells that this term leads to the additional heavy-hole lighthole mixing 43,44 , however in our case such additional mixing strength is more than order of magnitude weaker than mechanism presented in Eq. 1 The second part depends on the third power of the momentum operators and therefore will be referred to as the cubic term of the LK Hamiltonian.…”
Section: Theoretical Modelmentioning
confidence: 56%
“…The first term in the above Hamiltonian will be further called Zeeman part of the LK Hamiltonian because of its similarity to standard Zeeman Hamiltonian. It is well known from studies of quantum wells that this term leads to the additional heavy-hole lighthole mixing 43,44 , however in our case such additional mixing strength is more than order of magnitude weaker than mechanism presented in Eq. 1 The second part depends on the third power of the momentum operators and therefore will be referred to as the cubic term of the LK Hamiltonian.…”
Section: Theoretical Modelmentioning
confidence: 56%
“…, where -directions, i.e., a reflection of the cubic symmetry of the host lattice). Based on the previous experience, 8,17 we believe that the function Eq. ( 2)…”
Section: Models and Resultsmentioning
confidence: 99%
“…9 In practice, however, the transverse g factor of heavy holes in QDs and in QWs is often determined by structural distortions in the plane of the layer. [10][11][12] Possible sources of such distortions are the anisotropy of the localizing potential ͑e.g., shape anisotropy of the QDs͒, fluctuations in local distribution of strain of the atomic bonds ͑uniaxial in-plane deformations͒, or a combination of both these factors. Recent studies have shown that the effect of deformations is probably more pronounced in QDs.…”
mentioning
confidence: 99%